Test Kirinyuh Leaf Extract (Euphatorium odoratum.L) as Biofungicides against Antracnose Disease (Colletotrichum capsici) on Chili Plants (Capsicum Annum L) - Asmah Indrawati (Budapest International Research and Critics University, 2021)
Research to determine the effectiveness and concentration of extracts E. odoratumas a biofungicide applied to red chilli (C. Annum L) which is attacked by anthracnose (C.capsici). The research was carried out for 4 months from January to April 2020 at the Microbiology Laboratory of the University of North Sumatra, at the UMA Plant Protection Laboratory and in the Experimental Field of the Faculty of Agriculture, Medan Area University. The research was conducted using experimental methods, namely direct experiments and carried out in 2 stages: in vitro and in vivo. In the in vitro research stage, using a completely randomized non-factorial design (CRD Non Factorial) 9 levels with 1 factor which was repeated 3 replications, namely giving E. odoratum extract consisting of: AF0- = negative control (without treatment), AF0 + = Control positive (0.2% synthetic fungicide), AF1 = PDA media with 10% E. odoratum extract, AF2 = PDA media with 20% E. odoratum extract, A3 = PDA media with 30% E. odoratum extract, AF4 = PDA media with 40% E. odoratum extract, AF5 = PDA media with 50% E. odoratum extract, AF6 = PDA media with 60% E. odoratum extract, AF7 = PDA media with 70% E. odoratum extract. In the In vivo stage, the experiment used a non-factoral randomized block design (non factorial shelf) with the treatment factor of E. odoratum extract obtained from the results of experiments in vitro in the laboratory, namely the concentration of 0%, 50%, 60% and 70%, which is the level of The extract concentration was below the effective concentration and the optimum extract concentration (best from the In vitro results) and the extract concentration was above optimal. Treatment replications and the number of treatment samples to be carried out were based on the results of the concentration to be applied and determined the level in a Non-factorial Randomized Block Design (Non-factorial RBD). ResultIn laboratory experiments showed that the extract was administered E. odoratum with a concentration of 60% and 70% significantly suppressed the growth of C. capsici colonies up to 0 cm2. The ability to suppress (inhibit) the growth of C. capsici is more effective than the use of synthetic fungicides. In field experiments, it can be concluded that the application of 70% E. odoratum extract has a very significant effect on fruit production and anthracnose attack intensity.